Perlindungan Hukum Terhadap Satpol PP Dalam Korban Penganiyaan Yang Dilakukan Oleh Oknum Buruh Pada Aksi Unjuk Rasa Kenaikan Upah Minimum Kota Surabaya (UMK) - Trixie Nadya Dwijayanti; Mega Dewi Ambarwati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Public Order is an important aspect in making progress into victory. To address this, an arrangement was established in the form of a Territorial Directive which is expected to play an important role in overcoming problems of collective agreement, and an institution or device was created that can assist the Territorial Head. in ensuring peace and harmony in the city of Surabaya. This article aims to provide legal direction that regulates legal security for victims. The cruel actions carried out by the intensifiers when carrying out demonstrations that occurred due to mishandling clearly indicate a failure or several violations of the framework, including human rights which were clearly controlled in several pre-existing directions. It asks about employment. This writing uses a normative juridical method with a conceptual and regulatory approach. The results of the writing show that the conclusion is that freezing every citizen, for individuals and non-individuals, can be a change from a country where the majority has power in social, state and state life and this has been directed at good legal structure and control. broadly and globally. This means that the state guarantees the right of every citizen to communicate conclusions or the life span of society in a safe, efficient, peaceful and peaceful manner, so that there can be no more acts of a cruel or oppressive nature. whether from its components. open society and also police officers.